2004
DOI: 10.1093/carcin/bgh205
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin enhances Fas expression and apoptosis in the colon mucosa of azoxymethane-treated rats

Abstract: Bovine lactoferrin, a multifunctional glycoprotein, has been shown to strongly inhibit development of azoxymethane (AOM)-induced rat colon tumors. Little, however, is known about the inhibitory mechanisms. We have demonstrated recently that lactoferrin enhances the expression of a member of the tumor necrosis factor receptor family, Fas, in the colon mucosa during both early and late stages of carcinogenesis. Thus, Fas could be involved in bovine lactoferrin-mediated inhibition of tumor development. To investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 41 publications
5
82
1
Order By: Relevance
“…This suggests that Lfc B is present in the Lfn-p fraction and is also implicated as an apoptotic stimulus in SAS cells. Recently, the role of activation of caspase-3, one of the most common mediators of apoptosis, in Lfn-induced apoptotic change was studied in the colon mucosa of azoxymethane-treated rats (10). The authors also reported that caspase-3 activation was the result of induction of Fas, a member of tumor necrosis factor (TNF) receptor family, and activation of caspase-8, an initiator caspase for caspase-3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that Lfc B is present in the Lfn-p fraction and is also implicated as an apoptotic stimulus in SAS cells. Recently, the role of activation of caspase-3, one of the most common mediators of apoptosis, in Lfn-induced apoptotic change was studied in the colon mucosa of azoxymethane-treated rats (10). The authors also reported that caspase-3 activation was the result of induction of Fas, a member of tumor necrosis factor (TNF) receptor family, and activation of caspase-8, an initiator caspase for caspase-3.…”
Section: Discussionmentioning
confidence: 99%
“…Bovine Lfc induces apoptotic cell death by producing reactive oxygen species (ROS) in human leukemia cell lines in vitro (8). Recently, it was found that Lfn changed apoptosis-related gene expression in colon mucosa (10) and a head/ neck cancer cell line (11). However, the exact mechanism underlying cell death induced by Lfn and Lfc remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the exact mechanism of this function has not been discovered so far (Fujita et al, 2004).…”
Section: Lactoferrin and Tumor Growthmentioning
confidence: 99%
“…Lactoferrin inhibit the proliferation of cancer cells by various mechanisms. One of such mechanism includes that it interacts with polysaccharides ligands on cell surfaces and activate cell signaling pathways such as the Fas pathway thereby inhibit the growth of tumor by apoptosis [93]. Lactoferrin can also penetrate cells and function as a transcription factor and activating the transcription of specific DNA sequences [38,94].…”
Section: Apoptotic Effectmentioning
confidence: 99%